PENGARUH TRANSFER PRICING, ROA, LEVERAGE DAN MANAJEMEN LABA TERHADAP PENGHINDARAN PAJAK DI BEI TAHUN 2017-2021 - Sylvania Salsabilla; Fajar Nurdin (Jurnal Ilmiah Akuntansi Peradaban, 2023)
This research aims to analyze the effect of transfer pricing, ROA, leverage, and earning management on tax avoidance in mining sector companies listed on the BEI in 2017-2021. This research used a quantitative method basic on secondary data with sampling method using purposive sampling technique, obtained from 95 data on financial statements from 19 companies. The statistical analysis method used in this research is Partial Least Square (PLS) using SmartPLS 3.0. The result partially showed that transfer pricing and leverage have an effect on tax avoidance, while ROA and earning management have no effect on tax avoidance. Simultaneously showed that variable transfer pricing, ROA, leverage, and earning management have no effect on tax avoidance.